340 Cancer incidence and mortality among underground and surface gold miners in Western Australia. (11th October 2013) - Peters,; Reid, A; Fritschi, L; Musk, A W; Klerk, N de
Abstract : Background: The Kalgoorlie gold miners' cohort was established in 1994, consisting of all workers (males only) who attended workplace health surveys in 1961, 1962, 1974, and 1975. In this study the follow-up of the cohort has been extended to 2011. Our objectives were (i) to estimate cancer mortality and incidence, for both surface and underground miners; and (ii) to examine the hypothesis that (underground) mining may be protective against prostate cancer. Methods: Standardised mortality and incidence ratios (SMRs and SIRs) and 95% confidence intervals (95% CI) were calculated to compare cancer mortality and incidence of the former Kalgoorlie miners with that of the Western Australian male population. Internal comparisons on duration of underground work were examined using Cox regression. Results: During 52, 440 person-years of follow-up, 1, 922 deaths were observed. Increased mortality from any cause was observed for the miners (SMR = 1.34, 95% CI 1.28–1.40), with hazard ratios indicating a trend for duration working underground (p = 0.02). For any cancer, mortality was increased for the total group of miners (SMR = 1.25, 95% CI 1.14–1.37). In the Cox models, lung cancer mortality and incidence were particularly increased among underground miners, even after adjustment for smoking. The SMR for prostate cancer suggested a lower risk for underground miners, but this was not supported by the incidence data with a significantly increased incidence of prostate cancer (SIR = 1.26, 95% CI 1.03–1.54) among underground miners. Conclusions: Overall cancer mortality and incidence was higher among Western Australian gold miners compared with the general population, especially for lung cancer and particularly for underground mining. This study does not support the hypothesis that miners have a decreased risk of prostate cancer: the results indicate a positive association between working as a miner and prostate cancer.